NILAI-NILAI KEBANGSAAN DALAM NOVEL SEBELAS PATRIOT KARYA ANDREA HIRATA - Hendra Wijaya (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe national values in the Novel Sebelas Patriot  by Andrea Hirata. This research is a qualitative descriptive type research. The research data is in the form of quotations containing national values in the novel. The source of the data comes from a novel book entitled Sebelas Patriot  by Andrea Hirata. The step in data collection is carried out by reading data source books and source books related to the theory of national values and also literary theory to gain experience in collecting data, then marking findings in the form of quotations related to aspects to be studied, and classifying the findings of quotation data into a data classification table. The approach in this study uses a structural approach. The data analysis step is carried out by entering the classified quotation data into the data analysis table, then analyzing the research data in accordance with the theory taken from the theory of nationality values in the theory source book. Based on the results and discussions, in the study there are three aspects of national values which include: Human values, contained in the data, namely “Dengan membangkang, dia merasa telah membela abang-abangnya, membela bangsanya.” (SP:23). The value of unity, found in the data, namely “Tertindas di bawah penjajahan, rakyat menemukan caranya sendiri untuk melawan.” (SP:6). The value of patriotism, found in the data, namely “Dia menolak bergabung dengan tim penjajah kaumnya.“ (SP:23). From the results of this study, human values are the most dominating values among the other two values. These three values are found to vary within the novel.